Study on dermatoses and their prevalence in groups of confirmed alcoholic individuals in comparison to a non-alcoholic group of individuals Estudo das dermatoses e sua prevalencia em individuos comprovadamente alcoolistas comparativamente a um grupo de individuos não alcoolistas - Maria Cecilia Teixeira de Carvalho Bruno; Maria Aparecida Constantino Vilela; Carlos Alberto B. Mendes de Oliveira (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: The direct relationship between alcoholism and dermatoses has been evaluated in recent researches. However, there are few objective surveys that demonstrate and prove a direct relationship between alcohol and a specific dermatosis. OBJECTIVES: to verify the prevalence of dermatoses in alcoholics, analize the dermatological changes found in these patients and their evolution during alcoholic abstinence. Also, to compare the results obtained with a non-alcoholic control group and with the data found in medical literature. METHODS: the dermatologic conditions of 278 alcoholic patients (250 men, 28 women) were studied over a period of 4 years, and compared to those of a control group of 271 non-alcoholic individuals (249 men, 22 women), members of the Military Police Force. The individuals in both groups were between 20 and 60 years old. RESULTS: Pellagra, nummular eczema, purpura pigmentosa chronica (also known as pigmented purpuric dermatosis) and psoriasis were more frequent in the group of alcoholics and, apparently, occurred in parallel with alcoholism that seems to play a role in the evolution of these dermatoses. The dermatopathies were more frequent before the age of forty, regardless of factors such as profession, race or gender. CONCLUSION: the association of dermatoses and alcoholism was extremely significant according to the statistical data. Alcoholism can be considered a risk factor for pellagra, psoriasis, nummular eczema and purpura pigmentosa chronica dermatoses, which can, as well, be considered alcoholism indicators. FUNDAMENTOS: A relação direta entre o alcoolismo e as dermatoses vem sendo avaliada em recentes pesquisas. No entanto são poucos os estudos objetivos que demonstram e comprovam uma relação direta entre o álcool e uma determinada dermatose. OBJETIVOS: Verificar a prevalência de dermatoses em alcoolistas, avaliar as alterações dermatológicas encontradas nesses doentes e sua evolução frente abstinência alcoólica. Comparar os resultados obtidos com um grupo controle não alcoolista e com os resultados encontrados na literatura mundial. MÉTODO: Foram estudados, durante 4 anos, sob o ponto de vista dermatológico, 278 doentes alcoolistas (250 homens, 28 mulheres) comparativamente a 271 indivíduos (249 homens, 22 mulheres) não alcoolistas integrantes da Policia Militar, que constituíram o grupo controle, ambos com idades entre 20 e 60 anos. RESULTADOS: As dermatoses pelagra, eczema numular, púrpura pigmentosa crônica e psoríase foram mais frequentes no grupo dos alcoolistas e aparentemente surgiram paralelamente ao alcoolismo, que parece interferir na evolução destas dermatoses. As dermatopatias foram mais frequentes antes dos quarenta anos, não sendo significativos os fatores profissão, cor e sexo. CONCLUSÃO: a associação das dermatoses com alcoolismo foi altamente significativa, como indicaram os dados estatísticos. O alcoolismo pode ser considerado fator de risco para as dermatoses pelagra, psoríase, eczema numular e púrpura pigmentar crônica, podendo estas serem consideradas indicadoras de alcoolismo